A Review on Phytochemical Properties and Therapeutic Applications of Musa acuminata: Review Article (Journal of Pharma Insights and Research, 2024)
Musa acuminata, a perennial tree-like plant of the Musaceae family, grows extensively across tropical and subtropical regions worldwide. Bananas serve as a vital crop in numerous countries due to their nutritional density and medicinal properties both as a fruit and vegetable source. M. acuminata contains diverse bioactive compounds including myricetin, apigenin glycosides, dopamine, N-acetyl serotonin, rutin, polyphenols, flavonoids, and various glycosides. Traditional medicine systems have employed different parts of M. acuminata to treat conditions such as fever, cough, bronchitis, dysentery, allergies, and sexually transmitted diseases. Modern pharmacological studies validate several therapeutic properties of M. acuminata, including antioxidant, antidiabetic, immunomodulatory, hypolipidemic, anticancer, and antimicrobial activities. The plant demonstrates significant cholesterol-reducing effects through compounds present in its peel, particularly flavonoids, tannins, and saponins. The antioxidant capacity of M. acuminata relates to its cell wall phenolic content, while its hepatoprotective and anti-ulcer properties rival conventional medications in animal models. The plant exhibits notable enzyme inhibition activities, particularly against alpha-glucosidase and acetylcholinesterase. M. acuminata also shows promising results against Leishmania species through its phytoalexin compounds